2020
DOI: 10.1042/bsr20191554
|View full text |Cite
|
Sign up to set email alerts
|

Comprehensive analysis of prognostic biomarkers in lung adenocarcinoma based on aberrant lncRNA–miRNA–mRNA networks and Cox regression models

Abstract: Lung adenocarcinoma (LUAD) is the leading cause of cancer-related death worldwide, and its underlying mechanism remains unclear. Accumulating evidence has highlighted that long non-coding RNA (lncRNA) acts as competitive endogenous RNA (ceRNA) and plays an important role in the occurrence and development of LUAD. Here, we comprehensively analyzed and provided an overview of the lncRNAs, miRNAs, and mRNAs associated with LUAD from The Cancer Genome Atlas (TCGA) database. Then, differentially expressed lncRNAs (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(12 citation statements)
references
References 49 publications
(50 reference statements)
0
12
0
Order By: Relevance
“…Numerous studies have demonstrated that cytoplasmic lncRNAs likely function as competing endogenous RNAs (ceRNAs) to serve as a "sponge/decoy" via miRNA binding and thereby increase miRNA target levels at the post-transcriptional level [25][26][27]. To understand the role of LINC00514 in promoting OS progression, we determined its subcellular localization in HOS and MG-63 cells.…”
Section: Linc00514 Functions As a Molecular Sponge For Microrna-708-5mentioning
confidence: 99%
“…Numerous studies have demonstrated that cytoplasmic lncRNAs likely function as competing endogenous RNAs (ceRNAs) to serve as a "sponge/decoy" via miRNA binding and thereby increase miRNA target levels at the post-transcriptional level [25][26][27]. To understand the role of LINC00514 in promoting OS progression, we determined its subcellular localization in HOS and MG-63 cells.…”
Section: Linc00514 Functions As a Molecular Sponge For Microrna-708-5mentioning
confidence: 99%
“…We then used DElncRNA, DEmiRNA and DEmRNA in this study to construct lncRNA-miRNA-mRNA associations, as previously reported [18,52]. (1) DElncRNA-DEmiRNA interactions were described by miRcode 11 [53].…”
Section: Cerna Network Constructionmentioning
confidence: 99%
“…Motifs reported on SOX protein data via MEME v5.0.5 [51]. SOX secondary structure was built by Secondary structure by NPS@: Network Protein Sequence Analysis online service [52].…”
Section: Example: Genome-wide Retrieval and Identification Of Sox Genmentioning
confidence: 99%
“…The crosstalk between 2 lncRNAs, 3 miRNAs, and 18 mRNAs revealed a complex mechanism in baicalin-treated MG63 cells. The ceRNA hypothesis explains a new mechanism of RNA interaction and provides important clues and theoretical guidance for further understanding the tumorigenesis mechanism [31] . We observed that lncRNAs sponge several miRNAs, while miRNAs could regulate more than one mRNA.…”
Section: Discussionmentioning
confidence: 99%
“…The genes with fold-change in expression > 2.0 and P < 0.05 between untreated and baicalin-treated samples were identi ed to be differentially expressed. In total, our project detected 58 lncRNAs, 31…”
Section: Delncrnas Demirnas and Demrnasmentioning
confidence: 99%